The politics of federal prosecution - Boyd, Christina L.; Boldt, Ethan D.; Ostrander, Ian; Nelson, Michael J. 1986- (Oxford University Press, 2021)
In February 2016, while testifying in a House Appropriations Subcommittee hearing, U.S. Attorney General Loretta Lynch, a Barack Obama appointee, promised that her department would act with independence in investigating Hillary Clinton's usage of a personal email server during her tenure as Secretary of State. During that hearing, Congressman John Carter (R-TX) asked Lynch: If the FBI makes the case that Hillary Clinton mishandled classified information and put America's security at risk, will you prosecute the case? . . .[P]lease look the American people in the eye and tell us what your position is as you are the chief prosecutor of the United States. In response to this questioning, Lynch asserted that: [The matter] is being handled by . . . independent attorneys in the Department of Justice. They follow the evidence, they look at the law and they'll make a recommendation to me when the time is appropriate. . .This will be conducted as every other case. We will review all the facts and all the evidence and come to an independent conclusion as how to best handle it. And I am also aware of no efforts to undermine our review or investigation into this matter at all (Goldman 2016). Despite strong claims of prosecutorial independence, many Republicans complained that a Department of Justice run by Obama appointees could not impartially pass legal judgment on the Hillary Clintonemails matter. A June 27, 2016 meeting between Lynch and former U.S. President Bill Clinton would not help matters. The two privately talked for approximately 20 minutes on a plane sitting on the Phoenix Sky Harbor airport tarmac in a meeting described as unplanned and "primarily social." Despite the meeting's claimed innocuous content, it "caused a cascading political storm" for Hillary Clinton's presidential campaign and "provided fodder for Republicans who have accused the Justice Department of bias in its inquiry into Secretary Clinton's use of a private email server at the State Department" (Chozick 2016). Even Democrats expressed concerns about the meeting Senator Chris Coons (D-DE) remarked that "I do think that this meeting sends the wrong signal . . . I think she should have steered clear, even of a brief, casual social meeting with the former president"--